Bipolar output direct‐coupled DC–DC converter applied to DC grids. Issue 16 (17th December 2018) - Guo, Lingyu; Yao, Gang; Huang, Chengjun; Zhou, Lidan
Abstract : The unipolar‐input bipolar‐output DC–DC converters with megawatt rating are the key equipment in the multi‐terminal HVDC and DC grids, especially in the DC wind farm. This paper presents a novel direct‐coupled transformerless DC–DC converter to interconnect unipolar DC system with bipolar DC transmission line based on cascaded sub‐modules. The sub‐modules can be achieved by active clamping (clamped diode), half bridge and full bridge. The proportional‐integral control strategy is employed to balance the capacitors' voltages in several sub‐modules and the energy between the upper and lower arms. Compared with other bipolar output DC–DC converters, the new direct‐coupled DC–DC converter offers several merits: (1) The volume and the cost can be reduced due to the absence of the transformer and the large‐scale sub‐module capacitance; (2) There is no extra AC–DC conversion process, so it can achieve higher efficiency; (3) The IGBTs only turn on or off once in a period, which results in lower power loss; (4) High step‐up ratio, redundancy, and fault tolerance can be achieved by changing the number of sub‐modules. Finally, the simulation of the proposed DC–DC converter based on MATLAB/Simulink platform is given to verify the feasibility of the topology and the accuracy of the theoretical analysis.